The Effectiveness of Social-Emotional Competence Training on Social Skills and Empathy of Preschool Children - Farjam, Narjes Khaton; Emamirizi, Kobra (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to examine the effectiveness of social-emotional competence training on social skills and empathy among preschool children in Shahreza. Methods and Materials: The research employed a quasi-experimental design with an experimental group and a control group, using a pre-test and post-test approach. The sample consisted of 30 preschool children selected through non-random convenience sampling and divided equally into the experimental (n = 15) and control (n = 15) groups. The experimental group received social-emotional competence training across eight sessions, each lasting 45 minutes. Data were collected using the Empathy Questionnaire (Yong et al., 2009) and the Social Skills Rating System—Teacher Form (Gresham & Elliott, 1990). Analysis was conducted using analysis of covariance (ANCOVA). Findings: The results of the analysis of covariance (ANCOVA) demonstrated that social-emotional competence training had a significant effect on social skills and empathy in the experimental group compared to the control group. Specifically, for total social skills, there was a significant difference between the experimental and control groups in the post-test, F(1, 27) = 47.09, p < .001, η² = .636, indicating a large effect size. Significant improvements were also observed in the individual components: self-control, F(1, 27) = 77.02, p < .001, η² = .740; cooperation and empathy, F(1, 27) = 58.08, p < .001, η² = .683; assertiveness, F(1, 27) = 69.22, p < .001, η² = .719; and responsibility, F(1, 27) = 4.03, p = .045, η² = .430. Additionally, for empathy, the experimental group showed a significant increase in post-test scores, F(1, 27) = 22.43, p < .001, η² = .454, demonstrating a medium to large effect. These findings confirm the efficacy of the training program in enhancing social and emotional competencies. Conclusion: Social-emotional competence training is effective in improving social skills and empathy among preschool children. The results support the integration of structured social-emotional training programs in early childhood education to promote social and emotional development. Early interventions may yield lasting benefits, equipping children with essential skills for academic and social success.